Rural Livelihoods, Resources and Coping with Crisis in Indonesia: A Comparative Study - Milan J. Titus; Paul P. M. Burgers (Amsterdam University Press, 2009)
Most literature on the economic crisis in indonesia has focused on the negative macro-economic impacts during the "crisis- years" of 1997-99. The case studies presented in this book take a different perspective. With a longitudinal research perspective, this comparative study analyses a wide variety of responses to the crisis among communities and households. The case studies in this book cover the coping and adapting mechanisms of rural households under a variety of resource use practices and resource use regulations in different areas of Indonesia.
Keywords: 330; Public administration; Economics; Political science; Ländlicher Raum; Soziale Lage; Ernährungssicherung; Lebensstandard; Wirtschaftskrise; Umweltbelastung; Regionalentwicklung; Indonesien